2022
DOI: 10.3389/fpsyt.2022.893097
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio, Platelet-to-Lymphocyte Ratio, and Monocyte-to-Lymphocyte Ratio in Depression: An Updated Systematic Review and Meta-Analysis

Abstract: BackgroundResearch on neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and monocyte-to-lymphocyte ratio (MLR) in depression is still emerging and has increased 3-fold since the first meta-analysis. An updated meta-analysis with sufficient studies can provide more evidence for a potential relationship between NLR, PLR, MLR, and depression.MethodsWe identified 18 studies from the PubMed, EMBASE, Cochrane library, and Web of Science databases. Meta-analyses were performed to generate pool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 105 publications
3
13
0
Order By: Relevance
“…Previous studies have found low-grade systemic inflammation in adult psychiatric inpatients, especially for those diagnosed with schizophrenia and bipolar disorder (BD) [ 11 ]. According to an updated systematic review and meta-analysis of major depressive disorder (MDD) on patient groups in China, the NLR, PLR, and MLR were all elevated in patients with depression, as compared with healthy controls [ 21 ]. These markers are also involved in the inflammatory pathophysiology among children and adolescents with psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found low-grade systemic inflammation in adult psychiatric inpatients, especially for those diagnosed with schizophrenia and bipolar disorder (BD) [ 11 ]. According to an updated systematic review and meta-analysis of major depressive disorder (MDD) on patient groups in China, the NLR, PLR, and MLR were all elevated in patients with depression, as compared with healthy controls [ 21 ]. These markers are also involved in the inflammatory pathophysiology among children and adolescents with psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, more and more researchers have paid more attention to the MLR as a biomarker. For example, Cheng et al found that MLR was significantly associated with an increased risk of depression 19 . Huang et al found that MLR was associated with a 2-year relapse in patients with multiple sclerosis 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this elevated neutrophil and low lymphocyte participation can be expressed in the neutrophil-lymphocyte ratio (NLR), which, according to recent studies, could be a novel and clinically relevant biomarker used to indicate a higher risk of depression and to predict poor 3-month functional outcomes in ischemic stroke patients [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%